Homeownership, Community Interactions, and Segregation - Hoff, Karla; Sen, Arijit (American Economic Review, 2005)
We show that individuals with identical preferences and abilities can self-organize into communities with starkly different civic environments. Specifically, we consider a multi-community city where community quality depends upon residents' efforts to prevent crime, improve local governance, etc. Homeownership raises incentives for such civic efforts, but is beyond the reach of the poor. Within-community externalities lead to segregated cities: the rich reside in healthy homeowner communities, while the poor live in dysfunctional renter communities. Tenure segregation in the United States accords well with our prediction. We study alternative tax-subsidy policies to expand homeownership and to promote integration of homeowners and renters.